Optimalisasi Efisiensi Operasional: Pendekatan Srategis Akuntansi Manajemen Di Mini Market So Mart - Zakwan Zahran; Alika Ragnavilia Aphrodite; Ratih Kusumastuti (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research describes the optimization of operational efficiency of the "So Mart" minimarket through a management accounting strategy approach. The main purpose of this research is to identify and analyze possibilities for improving operational efficiency from a management accounting perspective. Research methods include internal research, cost analysis, and evaluation of existing accounting information systems. Research shows that implementing integrated management accounting strategies improves inventory monitoring, price adjustments, and more effective inventory management. By optimizing this process, “So Mart” can reduce operational costs, increase profitability, and strengthen its competitive position in the mini market market. The findings of this research provide practical guidance for mini market shop owners to utilize management accounting strategies to increase operational efficiency. Theoretical implications also contribute to the management accounting literature by considering the practical application of these concepts in small retail businesses.